Pandemic Unveils Transportation Sector's Financial Resilience: Pandemi Mengungkap Ketahanan Finansial Sektor Transportasi - Putri Dewi Rohmawati; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2022, specifically focusing on the impact of the Covid-19 pandemic. Analyzing key financial ratios including Return On Assets (ROA), Current Ratio (CR), Debt To Equity Ratio (DER), and Total Asset Turnover (TATO), the research aims to identify differences in performance before and during the pandemic. Utilizing a comparative research design and employing the Wilcoxon signed rank test for data analysis, findings reveal a significant decrease in Total Asset Turnover during the pandemic, indicating decreased asset efficiency. However, no significant differences were observed in ROA, CR, and DER, suggesting relatively stable profitability, liquidity, and solvency ratios despite the challenges posed by the pandemic. These results offer valuable insights for industry stakeholders, policymakers, and investors, aiding in strategic decision-making and resilience planning for future crises. Highlight: Examines financial performance of transportation companies during Covid-19 pandemic. Significant decrease in Total Asset Turnover (TATO) during pandemic. Stability observed in ROA, CR, and DER despite pandemic challenges. Keyword: Transportation industry, Financial performance, Covid-19 pandemic, Indonesia Stock Exchange (IDX), Comparative research.